KESETARAAN GENDER DALAM IJTIHAD HUKUM WARIS DI INDONESIA - Sugiri Permana (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2018)
AbstractThe discourse on Islamic law has always been the public attention, both from the standpoint of fiqh, as well as other legal side (civil/ common law, customary or feminism). Ijtihad as part of legal reform, is an important part of the dynamics of inheritance law from the time of as-shahabh (the companions) to this day. This paper attempts to describe the development of inheritance law in Indonesia. Some thoughts on equality in inheritance law are part of ijtihad object of legal experts as well as developments in Court decisions.Key words:Fiqh, Ijtihad, Iquality, Renewal, InheritanceAbstrakDiskursus tentang hukum waris Islam selalu menjadi perhatian publik, baik dari sudut pandang fikih, maupun sisi hukum lainnya (hukum Barat, adat atau feminisme). Ijtihad sebagai bagian dari pembaharuan hukum, menjadi bagian penting dalam dinamika hukum waris mulai dari zaman sahabat hingga saat ini. Tulisan ini mencoba mendeskripsikan perkembangan hukum waris di Indonesia. Beberapa pemikiran tentang kesetaraan dalam hukum waris menjadi bagian objek ijtihad para ahli hukum termasuk juga perkembangan dalam putusan Pengadilan.Kata Kunci: Fikih, Ijtihad, Kesetaraan, Pembaharuan, Waris